2017
DOI: 10.3126/ije.v6i1.16867
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Hazards in Municipal Solid Waste Collecting Workers of Chandrapur City, Central India

Abstract: Solid waste management has important occupational health issues associated with it. Out of 204 solid waste collecting workers of Chandrapur Municipal Corporation, 20 workers were selected (10% of the population) as sample size (15 female and 5 male) and 10 individuals as control group (5 female and 5 male). The study was carried out from November 2015 to January 2016. Peak Expiratory Flow Rate analysis was carried out through Breath-o meter and identification and assessment of other occupational health hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…17 The reason for the high magnitude of occupational health symptoms in this study compared to other previous studies done might be due to the nature and type of municipal solid waste being collected and its quantity, the duration of time staying in the workplace, type of PPE used on duty, and the nature of the topography/road that the waste was being collected from in Addis Ababa. This study showed that most municipal solid waste collectors suffered with different types of health symptoms such as respiratory symptoms (130 (45.0%)), skin symptoms (101 (34.2%)), and musculoskeletal symptoms (64 (21.8%)), which were higher than studies done in Central India (21% respiratory symptoms and 31.4% skin symptoms), 18 in Hebron, Palestine (44.7% respiratory symptoms and 20.2% skin symptoms), 6 and in Kathmandu, Nepal (13.8% respiratory symptoms and 15.5% skin symptoms). 19 Similarly, a study done in Beni-Suef, Egypt, revealed that respiratory and skin symptoms were 18.1% and 13.8%, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…17 The reason for the high magnitude of occupational health symptoms in this study compared to other previous studies done might be due to the nature and type of municipal solid waste being collected and its quantity, the duration of time staying in the workplace, type of PPE used on duty, and the nature of the topography/road that the waste was being collected from in Addis Ababa. This study showed that most municipal solid waste collectors suffered with different types of health symptoms such as respiratory symptoms (130 (45.0%)), skin symptoms (101 (34.2%)), and musculoskeletal symptoms (64 (21.8%)), which were higher than studies done in Central India (21% respiratory symptoms and 31.4% skin symptoms), 18 in Hebron, Palestine (44.7% respiratory symptoms and 20.2% skin symptoms), 6 and in Kathmandu, Nepal (13.8% respiratory symptoms and 15.5% skin symptoms). 19 Similarly, a study done in Beni-Suef, Egypt, revealed that respiratory and skin symptoms were 18.1% and 13.8%, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…This may cause air movement and release the biological particles during the production process. An important source of microorganisms in the industrial work environment are technological processes such as wastewater treatment, waste collection and processing, and biomass extraction and processing (Bawiec et al 2016;Vantarakis et al 2016;Patil and Kamble 2017;Han et al 2018;Paśmionka 2020). In urban waste water, apart from typically environmental microorganisms, there may also be pathogenic species from the genera Streptococcus, Helicobacter, Legionella, or Salmonella.…”
Section: Bioaerosols In the Premises Of Plants Processing Materials Of Plant Originmentioning
confidence: 99%
“…-Supervisors who are assigned to a mustering location or block to supervise the activities of the above waste workers. Waste workers face numerous occupational hazards, such strains from lifting, injuries from sharp objects and contact with pathogens when manually handling the wastes (Patil &Kamble, 2017). Workers are exposed to a wide variety of health hazards, which can occur via skin contact, injection, ingestion and inhalation (Health and Safety Executive, 2007;Tchobanoglous & Kreith, 2002;Suleman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%